2014
DOI: 10.1063/1.4879416
|View full text |Cite
|
Sign up to set email alerts
|

Exchange bias in phase-segregated Nd2/3Ca1/3MnO3 as a function of temperature and cooling magnetic fields

Abstract: Exchange bias (EB) phenomena have been observed in Nd 2/3 Ca 1/3 MnO 3 colossal magnetoresistance perovskite below the Curie temperature T C ~ 70 K and attributed to an antiferromagnetic (AFM) -ferromagnetic (FM) spontaneous phase segregated state of this compound. Field cooled magnetic hysteresis loops exhibit shifts toward negative direction of the magnetic field axis. The values of exchange field H EB and coercivity H C are found to be strongly dependent of temperature and strength of the cooling magnetic f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 43 publications
(52 reference statements)
2
20
1
3
Order By: Relevance
“…30 Magnetic hysteresis was measured at 10 K for the parent Nd 2/3 Ca 1/3 MnO 3 and the doped (Nd 0.9 Y 0.1 ) 2/3 Ca 1/3 MnO 3 compounds in the cases of zero field cooling (ZFC) and field cooling (FC) with H cool ¼ 0.5, 0.8, 1, 2, 5, 10 and 20 kOe. In contrast to our earlier studies, 13 where the magnetic hysteresis loops M(H) were measured between 6H cool , the data in the present study were obtained for 620 kOe. After each hysteresis measurement, the sample was heated to 320 K and kept at this temperature for 0.5 h.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…30 Magnetic hysteresis was measured at 10 K for the parent Nd 2/3 Ca 1/3 MnO 3 and the doped (Nd 0.9 Y 0.1 ) 2/3 Ca 1/3 MnO 3 compounds in the cases of zero field cooling (ZFC) and field cooling (FC) with H cool ¼ 0.5, 0.8, 1, 2, 5, 10 and 20 kOe. In contrast to our earlier studies, 13 where the magnetic hysteresis loops M(H) were measured between 6H cool , the data in the present study were obtained for 620 kOe. After each hysteresis measurement, the sample was heated to 320 K and kept at this temperature for 0.5 h.…”
contrasting
confidence: 52%
“…According to neutron diffraction data, the total amount of the AFM phase is about 82% and the fraction of the FM phase is about 18% at 4 K. 26 This low-temperature AFM-FM state with phase separation has been confirmed in studies using scanning SQUIDmicroscope. 27 Our previous studies have revealed the EB phenomenon in the compound Nd 2/3 Ca 1/3 MnO 3 , 13 which is closely related to spontaneous phase separation. The EB phenomenon depends non-monotonically on temperature and the cooling magnetic field, completely disappearing with the disappearance of the FM phase upon heating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The exchange bias field from the loop asymmetry along the field axis can be quantified as H EB ¼ À(H c1 þ H c2 )/2, where H c1 and H c2 are the left and right coercive fields, respectively. 5,27 The variation of H EB as a function of temperature in ZFC condition is shown in the inset of Figure 3(b). Notably, at 300 K, for nanoparticles having particle size of 40-100 nm, the exchange bias field is 79 Oe, which is significantly higher than the value reported in Ref.…”
Section: Resultsmentioning
confidence: 97%
“…2,4,5,8 Phase separation in manganites may have two origins: 1) electronic (microscopic) phase separation between phases with different charge carrier densities, which result in nanometer scale coexisting clusters, and 2) disorder-induced phase separation with percolative characteristics between equal-density phases, driven by disorder near first-order phase transitions. 2,[9][10][11][12][13][14][15] The latter leads to coexisting clusters as large as a micrometer in size. It has become clear by now that first-order phase transformations, which result in the coexistence of two crystalline phases in a wide temperature range (so-called martensitic transformations), play an important role in the physics of manganites.…”
Section: Introductionmentioning
confidence: 99%